Echocardiography-Guided Percutaneous Patent Ductus Arteriosus Closure: 1-Year Single Center Experience in Indonesia - Siagian, Sisca Natalia; Prakoso, Radityo; Putra, Bayushi Eka; Kurniawati, Yovi; Lelya, Olfi; Sembiring, Aditya Agita; Atmosudigdo, Indriwanto Sakidjan; Roebiono, Poppy Surwianti; Rahajoe, Anna Ulfah; Harimurti, Ganesja Moelia; Mendel, Brian; Christianto, Christianto; et al. (Frontiers in Cardiovascular Medicine, 2022)
Introduction: Since the first successful percutaneous closure under transoesophageal echocardiographic (TEE) guidance, many centres explored transcatheter procedures without fluoroscopy. This single centre study aims to show the feasibility and safety of percutaneous patent ductus arteriosus (PDA) closure under echocardiography-only guidance during our one-year experience. Methods: Patients with PDA were recruited for percutaneous PDA closure guided by either fluoroscopy or echocardiography-only in National Cardiovascular Center Harapan Kita (ClinicalTrials.gov Identifier: NCT05321849. URL: clinicaltrials.gov/ct2/show/NCT05321849). Patients were evaluated clinically and radiologically using TTE at 6, 24 and 48 hours after the procedure. Primary endpoint was the procedural success. Secondary endpoints were the procedural time and the rate of adverse events. Results: A total of 60 patients underwent transcatheter PDA closure, 30 patients with fluoroscopy and 30 patients with echocardiography guidance. All patients had successful PDA closure. There were only residual shunts which disappeared after follow-up in both groups, but one patient with fluoroscopy-guided procedure had moderate tricuspid regurgitation with suspected thrombus in the tricuspid valve. The procedural time were not significantly different between fluoroscopy and echocardiography group. Conclusion: Echocardiography-guided PDA closure is non-inferior to fluoroscopy-guided PDA closure, with similar procedural times. However, this method is operator-dependent and requires an experienced team for it to be performed successfully.